Integrated negative electrode binder for silicon-based negative electrode, negative electrode plate and lithium battery
By using specific amphiphilic polyacrylic acid copolymers and silicon-based negative electrode binders of conductive materials in lithium-ion batteries, a physical and chemical network is formed, which solves the problem of mechanical performance degradation caused by the expansion of silicon-based negative electrodes and improves the cycle stability of the battery and conductivity.
Patent Information
- Application Number
- CN202411803204.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The decline in mechanical properties and damage to the conductive network caused by expansion and contraction of silicon-based anode materials in lithium-ion batteries limits the energy density and cycling stability of lithium-ion batteries.
Using an integrated negative electrode binder for silicon-based negative electrode, including amphiphilic polyacrylic acid copolymer and conductive material of a specific molecular weight, to form a physical and chemical network to inhibit the expansion of silicon-based negative electrode and pass the uniformity of polymer and conductive material. Dispersion improves conductivity and adhesion.
It effectively improves the mechanical properties of the silicon-based negative electrode, suppresses the stress caused by expansion, extends the cycle life of the battery, reduces electrochemical polarization, and improves the overall performance of the battery.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of electrode sheets, and in particular to an integrated negative electrode binder, negative electrode slurry, negative electrode sheet and lithium battery for a silicon-based negative electrode. Background Art
[0002] With the rapid development of electric vehicles, portable electronic devices and other markets, higher requirements are placed on the energy density, cycle stability and safety of lithium-ion batteries. As an important component of lithium-ion batteries, the performance of negative electrode materials directly affects the overall performance of the battery.
[0003] At present, graphite anode is almost the only choice for commercial lithium-ion battery anode materials, but the shortcomings of graphite anode seriously restrict the further development of lithium-ion batteries. Since the first successful commercialization of graphite anode in 1991, with the progress of research and technology, the actual specific capacity of commercial graphite anode has been close to its theoretical specific capacity of 372 mAh g −1 In order to obtain higher energy density, people are in urgent need of finding a substitute for graphite. Among the common traditional negative electrode materials, silicon-based negative electrodes have a theoretical specific capacity that is almost 10 times that of graphite (4200 mAh g −1 , Li 22 Si5) and a lower lithium insertion potential (~0.2 V vs.Li + / Li). In addition, silicon is the second most abundant element in the earth's crust, and its abundant mineral resources are also conducive to its large-scale industrial production. Although silicon has a high theoretical specific capacity, when forming Li-Si alloys, silicon particles will expand to 300% to 400% of their original volume.
[0004] Therefore, the uninterrupted two-phase changes brought about by the long-term expansion and contraction cycle of silicon-based materials cause the internal stress of the material to accumulate continuously, which will eventually lead to the cracking and pulverization of Si particles. At the same time, due to the volume change characteristics of Si particles, the Si particles will continuously destroy the connection with the conductive network when used in the negative electrode structure, causing the electrochemical performance of the battery to continuously deteriorate during the cycle process. Therefore, it is extremely necessary to research and develop an integrated binder that can improve the mechanical properties of silicon negative electrodes, dissipate the stress generated by the volume expansion of silicon particles, thereby avoiding the breakage of silicon particles, and have good adhesion to conductive carbon materials. Summary of the invention
[0005] In order to improve the mechanical properties of silicon negative electrodes, dissipate the stress generated by the volume expansion of silicon particles to avoid the breakage of silicon particles, and have good adhesion to conductive carbon materials, the present application provides an integrated negative electrode binder for silicon-based negative electrodes, a negative electrode sheet and a lithium battery made thereof.
[0006] In a first aspect, the present application provides an integrated negative electrode binder for a silicon-based negative electrode, which adopts the following technical solution: An integrated negative electrode binder for a silicon-based negative electrode comprises a polymer and a conductive material; the polymer comprises a polyacrylic acid copolymer modified with a hydrophilic block and a hydrophobic block, the weight average molecular weight of the polymer is 600,000-800,000, the number average molecular weight is 300,000-500,000, and the polydispersity of the polymer is 1.2-2.5.
[0007] By adopting the above technical scheme, the negative electrode binder of the present application contains an amphiphilic polyacrylic acid copolymer with a specific molecular weight and a conductive material dispersed in the polyacrylic acid copolymer, which helps to improve the conductivity while simplifying the production process and reducing costs; and the negative electrode binder can form a physical and chemical network with the silicon-based negative electrode and the conductive agent, effectively inhibiting the expansion of the silicon-based negative electrode.
[0008] Optionally, the molecular weight of the hydrophilic block in the polyacrylic acid copolymer is 5000-25000 g / mol, and the molecular weight of the hydrophobic block is 15000-35000 g / mol.
[0009] When the molecular weights of the hydrophilic block and the hydrophobic block in the polyacrylic acid copolymer are within the above range, it is very beneficial to promote the dispersion of the conductive material in the polymer and can also improve the flexibility of the binder to a certain extent.
[0010] The hydrophilic block or hydrophobic block of the specific molecular weight can be obtained commercially, and the hydrophilic block or hydrophobic block of the corresponding molecular weight can be selected to participate in the polymerization to obtain the polyacrylic acid copolymer provided by the present invention.
[0011] Optionally, the glass transition temperature Tg of the polymer is 70-110°C.
[0012] When the glass transition temperature of the polymer is within the above range, it is very beneficial to improve the flexibility of the binder and inhibit the volume expansion of the negative electrode active material.
[0013] The hydrophilic block in the polyacrylic acid copolymer is selected from one or more of polyethylene glycol, polyoxyethylene ether, polyvinyl alcohol, polyvinyl pyrrolidone, polyacrylamide, sodium polyacrylate, and sodium polystyrene sulfonate; the hydrophobic block in the polyacrylic acid copolymer is selected from one or more of polymethyl methacrylate, polypropylene oxide, polystyrene, polysiloxane, polybutadiene, poly(methyl acrylate) and poly(butyl acrylate).
[0014] The acrylic acid monomer unit is obtained by polymerizing a monomer containing an acrylic acid group. Specifically, the acrylic acid monomer unit is selected from one or more of acrylic acid monomer units and methacrylic acid monomer units.
[0015] By adopting the above technical solution, acrylic monomers are used as the main monomers, and the linear polymers polymerized are composed of carbon chains and carboxyl functional groups, and the monomer carboxyl concentration is relatively high. The higher carboxyl concentration makes the connection between the bonding component and the silicon-based main material tighter, thereby improving the stability of the electrode structure.
[0016] Optionally, the hydrophobic block is selected from one or more of polymethyl methacrylate, polypropylene oxide, polystyrene, polysiloxane, polybutadiene, poly(methyl acrylate) and poly(butyl acrylate).
[0017] By adopting the above technical scheme, one or more of polyethylene glycol, polyoxyethylene ether, polyvinyl alcohol, polyvinyl pyrrolidone, polyacrylamide, sodium polyacrylate, and sodium polystyrene sulfonate are used as hydrophilic blocks, which carry oxygen lone pairs of electrons and can provide binding sites for the conduction of lithium ions, which is beneficial to a more uniform distribution of lithium ions and reduces electrochemical polarization.
[0018] Optionally, the polyacrylic acid copolymer comprises acrylic acid monomer units, hydrophilic blocks and hydrophobic blocks; the mass ratio of the acrylic acid monomer units, hydrophilic blocks and hydrophobic blocks is (10-30): (5-20): (5-10).
[0019] In the present invention, the mass ratio of the acrylic monomer unit, the hydrophilic block, and the hydrophobic block can be determined by the mass of the raw materials of the acrylic monomer, the hydrophilic block polymer, and the hydrophobic block polymer involved in the polymerization.
[0020] Optionally, the polyacrylic acid copolymer further comprises an amide monomer unit and an unsaturated nitrile monomer unit, wherein the mass ratio of the acrylic acid monomer unit, the amide monomer unit and the unsaturated nitrile monomer unit is (10-30): (5-20): (1-10).
[0021] Similarly, in the present invention, the mass ratio of the acrylic acid monomer units, amide monomer units, and unsaturated nitrile monomer units can be determined by the mass of the raw materials of the acrylic acid monomers, amide monomers, and unsaturated nitrile monomers involved in the polymerization.
[0022] The amide monomer units are obtained by polymerizing monomers containing amide groups. Specifically, the acrylamide monomer units are selected from one or more of acrylamide monomer units, methacrylamide monomer units, N,N-dimethylacrylamide monomer units, N,N'-methylenebisacrylamide monomer units, N-hydroxymethylacrylamide monomer units, N,N-diethylacrylamide monomer units, N-isopropylacrylamide monomer units, N-(isobutyloxy)methacrylamide monomer units, and N-[(3-(dimethylamino)propyl]methacrylamide monomer units.
[0023] By adopting the above technical solution, acrylamide monomer units are used to introduce hydrophilic centers into lipophilic polymers to improve viscosity, and acrylamide monomer units carry amide groups that can form hydrogen bonds with hydroxyl groups on the surface of silicon particles to enhance stability.
[0024] The unsaturated nitrile monomer unit is obtained by polymerizing an unsaturated monomer containing a cyano group. Specifically, the unsaturated nitrile monomer unit is selected from one or more of acrylonitrile monomer unit, methacrylonitrile monomer unit, ethacrylonitrile monomer unit and styrene nitrile monomer unit.
[0025] In the structure of the negative electrode binder provided by the present invention, the unsaturated nitrile monomer unit helps to further improve the stability of the negative electrode binder.
[0026] Optionally, the conductive material is a carbon nanotube; the carbon nanotube has a diameter of 1-30 nm and an aspect ratio greater than 3000.
[0027] The carbon nanotubes with the above-mentioned specific diameter and aspect ratio can be directly obtained commercially.
[0028] By adopting the above technical solution, when carbon nanotubes with the above tube diameter and aspect ratio are used, good dispersion of the carbon nanotubes in the polymer can be ensured, adhesion between the polymer and the conductive material can be ensured, and it is very beneficial to build a good conductive network, reduce the polarization resistance of the battery, and improve the cycle performance of the battery.
[0029] Optionally, the mass ratio of the polymer to the conductive material is (5-20): (1-3).
[0030] The binder provided by the present invention can be prepared by a method commonly used in the field of chemical synthesis, for example: The following raw materials are uniformly mixed in weight: 5-20 parts of polymer, 1-3 parts of conductive material and 1-10 parts of solvent.
[0031] The polymer can be obtained by copolymerizing the following raw materials: a hydrophilic block polymer, a hydrophobic block polymer, an acrylic monomer, selectively added acrylamide monomers and unsaturated nitrile monomers, an initiator and a solvent; wherein the hydrophilic block polymer is 5-20 parts, the acrylamide monomer is 5-20 parts, the unsaturated nitrile monomer is 1-10 parts, the acrylic monomer is 10-30 parts, the hydrophobic block polymer is 5-10 parts, the initiator is 0.1-2 parts and the deionized water is 100-200 parts.
[0032] The preparation process of the polymer comprises the following steps: putting a hydrophilic block polymer, an acrylic monomer, a selectively added acrylamide monomer and an unsaturated nitrile monomer into a reaction kettle for uniform stirring, introducing nitrogen for deoxygenation, adding an initiator, initiating polymerization at 60-70° C. for 5-9 hours, then heating to 80-90° C., adding a hydrophobic block polymer under stirring for 1-3 hours, then continuing to react at 80-100° C. for 2-4 hours, cooling and discharging the material to obtain an amphiphilic polymer.
[0033] The polymer, the conductive material and the solvent are put into a homogenizer according to the above ratio, and are homogenized and dispersed for 0.5-3 hours under circulating cooling to obtain the negative electrode binder provided by the present invention.
[0034] In the above method, the solvent is deionized water. Optionally, the initiator is selected from one or more of ammonium persulfate, potassium persulfate, sodium persulfate, ammonium sulfate, trimethylamine, benzoyl peroxide and di-tert-butyl peroxide.
[0035] In a second aspect, the present application provides a negative electrode sheet, which adopts the following technical solution: A negative electrode sheet, comprising a negative electrode active material and a binder; The binder includes the negative electrode binder described above.
[0036] Optionally, the weight ratio of the negative electrode active material to the binder is (95.5-97.5):(2.5-4.5).
[0037] The negative electrode active material includes graphite and silicon-carbon material in a weight ratio of (85-91):(9-15).
[0038] Preferably, the negative electrode sheet further comprises sodium carboxymethyl cellulose and styrene-butadiene rubber, and the weight ratio of the negative electrode binder, sodium carboxymethyl cellulose and styrene-butadiene rubber is (1-3): (0.5-1): (0.5-1).
[0039] In a third aspect, the present application provides a lithium battery, which adopts the following technical solution: A lithium battery comprises a positive electrode sheet and the negative electrode sheet mentioned above.
[0040] In summary, this application has the following beneficial effects: 1. In the negative electrode binder of the present application, an amphiphilic polyacrylic acid polymer is obtained by copolymerization, and then uniformly dispersed with carbon nanotubes, thereby overcoming the problem that carbon nanotubes are easy to agglomerate in the binder. Uniform dispersion can be achieved without adding additional dispersants, which helps to improve the conductivity while simplifying the production process and reducing costs. In addition, the binder can form a physical and chemical network with the silicon-based negative electrode and the conductive material, effectively inhibiting the expansion of the silicon-based negative electrode.
[0041] 2. Using acrylic monomers as the main monomer components, acrylonitrile helps to further improve stability, and adding hydrophilic blocks for copolymerization can introduce hydrophilic blocks into the side chains of polyacrylic acid polymers. The oxygen lone pairs of electrons on the hydrophilic blocks provide many binding sites for lithium ions, which can effectively reduce the polarization of the silicon negative electrode, promote the conduction of lithium ions, and improve the ionic conductivity of the negative electrode binder; adding hydrophobic blocks for copolymerization, due to the low surface energy characteristics of the hydrophobic blocks, can make the carbon nanotubes evenly dispersed while maintaining hydrophobicity, further improving the conductivity. DETAILED DESCRIPTION
[0042] The present application is further described in detail below in conjunction with specific embodiments.
[0043] The following raw materials in this application are all commercially available products, and are intended to fully disclose the raw materials of this application, and should not be construed as limiting the sources of the raw materials.
[0044] Specifically: polymethyl methacrylate CAS: 9011-14-7; polyethylene glycol CAS: 25322-68-3; acrylamide (CAS: 79-06-1; acrylonitrile CAS: 107-13-1; acrylic acid CAS: 79-10-7; graphite is commercially available from B&T Graphite, model AGP-2L-S; silicon carbon material is commercially available from Lanxi Zhide Silicon Carbon, model S0310; sodium carboxymethyl cellulose is commercially available from Weiyi 3000; styrene butadiene rubber is commercially available from Daoying A500; the conductive graphite in the conductive agent is commercially available from Super High Conductive Carbon Black SUPER P Li; single-walled carbon nanotubes are commercially available from Huijing SWCNT, with a tube diameter of 1-30nm and an aspect ratio of >3000; polypropylene oxide CAS number: 25322-69-4; polystyrene CAS number: 9003-53-6; poly(methyl acrylate) CAS number: 9003-21-8; sodium carboxymethyl cellulose CAS number: 9004-32-4, molecular formula: C8H 15 NaO8; styrene-butadiene rubber CAS number: 9003-55-8; polyvinyl alcohol CAS number: 9002-89-5; methacrylamide CAS number: 79-39-0; methacrylic acid CAS number: 79-41-4; potassium persulfate CAS number: 7727-21-1; polybutadiene; sodium polyacrylate CAS number: 9003-04-7; N,N-dimethylacrylamide CAS number: 2680-03-7; methyl acrylate CAS number: 96-33-3; sodium persulfate CAS number: 7775-27-1; polysiloxane CAS number: 63148-62-9.
[0045] Example 1
[0046] (1) Preparation of negative electrode binder: The negative electrode binder includes the following raw materials in weight which are uniformly mixed: 20 parts of polymer, 3 parts of conductive material and 10 parts of solvent.
[0047] The polymer is obtained by copolymerizing the following raw materials in weight: 8 parts of hydrophilic block polymer, 5 parts of acrylamide monomer, 5 parts of unsaturated nitrile monomer, 30 parts of acrylic monomer, 5 parts of hydrophobic block polymer, 0.5 parts of initiator and 100 parts of deionized water; The preparation process comprises the following steps: putting a hydrophilic block polymer, acrylamide monomer, acrylonitrile and acrylic acid monomer into a reaction kettle according to the above ratio, stirring and mixing, introducing nitrogen for 30 minutes to deoxygenate, adding an initiator, initiating polymerization at 65°C for 7 hours, then heating to 85°C, adding a hydrophobic block polymer under stirring for 2 hours, then continuing to react at 90°C for 3 hours, cooling and discharging, and obtaining an amphiphilic polymer; the weight average molecular weight and number average molecular weight of the polymer are 725001 and 396442 respectively detected by gel permeation chromatography, and the polydispersity of the polymer is 1.8288. At the same time, the glass transition temperature Tg is detected to be 91.15°C.
[0048] Wherein, the hydrophilic block polymer is polyethylene glycol (molecular weight of 10000-20000), the acrylamide monomer is acrylamide, the acrylic acid monomer is acrylic acid, the initiator is ammonium persulfate, the hydrophobic block polymer is polymethyl methacrylate (molecular weight of 20000-30000), and the unsaturated nitrile monomer is acrylonitrile; The conductive material is 2 parts of carbon nanotubes; the carbon nanotubes are single-walled carbon nanotubes with a tube diameter of 2 nm and an aspect ratio of >3000; The polymer, conductive material and deionized water were put into a homogenizer in a ratio of 20:3:10, and homogenized and dispersed for 1 hour under circulating cooling to obtain an integrated negative electrode binder for a silicon-based negative electrode.
[0049] (2) Preparation of negative electrode slurry: A negative electrode slurry, comprising 96 parts of negative electrode active material, 3 parts of integrated negative electrode binder for silicon-based negative electrode, 0.5 parts of sodium carboxymethyl cellulose and 0.5 parts of styrene-butadiene rubber; The negative electrode active material includes 86.4 parts of graphite and 9.6 parts of silicon carbon.
[0050] The preparation of negative electrode slurry includes the following steps: The integrated negative electrode binder for silicon-based negative electrode, sodium carboxymethyl cellulose and styrene-butadiene rubber were added to a double planetary stirring tank, stirred at a speed of 4000 rpm for 40 minutes, kneaded and high-speed dispersed and vacuumed at 1000 rpm for 30 minutes to obtain a negative electrode slurry.
[0051] (3) Preparation of negative electrode sheet: The prepared negative electrode slurry is coated on a 6μm copper foil by a coating machine. After the electrode is dried, the single-sided surface density is 120g / m 2 , according to 1.6g / mm 3 After compaction density and rolling, the negative electrode sheet is obtained.
[0052] (4) Preparation of lithium batteries: The negative electrode sheet and the corresponding positive electrode sheet are made into a lithium-ion battery with a capacity of 2Ah through slitting, winding, liquid injection and formation processes.
[0053] Example 2-3 The difference from Example 1 is that in the preparation of the negative electrode binder, the raw material ratio of the negative electrode binder is different, and the other steps are the same as Example 1.
[0054] The raw material ratios of the negative electrode binders of Examples 1-3 are shown in Table 1.
[0055] Table 1 Raw material ratios of negative electrode binders of Examples 1-3
[0056] Example 4 The difference from Example 1 is that in the preparation of the negative electrode binder, the hydrophilic block polymer is polyvinyl alcohol (molecular weight 10,000-20,000), the acrylamide monomer is methacrylamide, the acrylic acid monomer is methacrylic acid, the initiator is potassium persulfate, and the hydrophobic block polymer (molecular weight 20,000-30,000) is polybutadiene.
[0057] Example 5
[0058] The difference from Example 1 is that in the preparation of the negative electrode binder, the hydrophilic block polymer (molecular weight of 10,000-20,000) is sodium polyacrylate, the acrylamide monomer is N,N-dimethylacrylamide, the acrylic acid monomer is acrylic acid, the initiator is sodium persulfate, and the hydrophobic block polymer (molecular weight of 20,000-30,000) is polysiloxane.
[0059] Comparative Example 1 The difference from Example 1 is that no hydrophilic block polymer is included in the preparation of the negative electrode binder.
[0060] Comparative Example 2 The difference from Example 1 is that no hydrophobic block polymer is included in the preparation of the negative electrode binder.
[0061] Comparative Example 3 The difference from Example 1 is that in the preparation of the negative electrode slurry, the amount of negative electrode binder is 0 kg, the amount of sodium carboxymethyl cellulose is 0.5 kg, and the amount of styrene-butadiene rubber is 3.5 kg.
[0062] Performance testing
[0063] 1. Peel force test: The peeling force test was carried out according to the method specified in GB / T2792-2014 "Test method for peel strength of adhesive tape".
[0064] (II) Cycle life test Here are the steps: 1. Leave at room temperature for 1 hour; 2. 1C constant current and constant voltage charging to 3.65V, cut-off current 0.05C; 3. Stand still for 10 minutes; 4. Discharge at a constant current of 1C to 2.0V and record the discharge capacity; 5. Stand still for 10 minutes; 6. 1C constant current and constant voltage charging to 3.65V, cut-off current 0.05C; 7. Repeat the cycle test until the battery capacity is less than 80% of the second cycle capacity.
[0065] (III) Fully charged expansion test of the electrode The test steps are as follows: 1. Leave at room temperature for 1 hour; 2. 1C constant current and constant voltage charging to 3.65V, cut-off current 0.05C; 3. Stand still for 10 minutes; 4. Disassemble the battery cell in the glove box, test the thickness of the negative electrode at full charge, and compare the thickness of the electrode after rolling to obtain the expansion rate of the electrode at full charge.
[0066] (IV) Electrode resistivity test: The test equipment is a pole piece resistance meter, the equipment model is Yuanneng Technology BER-2100, and the pole piece resistivity is tested by the pole piece resistance meter.
[0067] The performance tests were performed on the pole pieces or lithium batteries prepared in Examples 1-5 and Comparative Examples 1-3, respectively. The test results are shown in Table 2.
[0068] Table 2 Test results of Examples 1-5 and Comparative Examples 1-3
[0069] It can be seen from Examples 1 to 5 and Table 2 that Example 1 of the present application is a preferred example and there is no obvious substantial difference in the test results of Examples 1 to 3.
[0070] Combining Example 1 and Comparative Examples 1-2 and Table 2, it can be seen that Example 1 is superior to Comparative Examples 1-2. The reason may be that when the hydrophilic block polymer is not added (i.e., Comparative Example 1), the volume expansion of the silicon-carbon negative electrode active material cannot be effectively suppressed, resulting in a decrease in the cycle performance of the battery. When the hydrophobic block polymer is not added (i.e., Comparative Example 2), the carbon nanotubes are easily agglomerated and difficult to be directly blended evenly with the polyacrylic acid polymer, resulting in a decrease in conductivity.
[0071] It can be seen from Example 1 and Comparative Example 3 and Table 2 that Example 1 is better than Comparative Example 3. The reason for this is that when the integrated negative electrode binder for the silicon-based negative electrode provided by the present invention is not added, it is difficult to form an effective network structure in the negative electrode material, making it difficult to suppress the expansion and contraction of the silicon negative electrode during the charge and discharge process, resulting in decreased performance in terms of peeling force, cycle life, expansibility and resistivity.
[0072] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. An integrated negative electrode binder for a silicon-based negative electrode, characterized in that: including polymers and conductive materials; The polymer comprises a polyacrylic acid copolymer modified with a hydrophilic block and a hydrophobic block, the weight average molecular weight of the polymer is 600,000-800,000, the number average molecular weight is 300,000-500,000, and the polydispersity of the polymer is 1.2-2.
5.
2. The integrated negative electrode binder for a silicon-based negative electrode according to claim 1, characterized in that: The molecular weight of the hydrophilic block in the polyacrylic acid copolymer is 5000-25000 g / mol, and the molecular weight of the hydrophobic block is 15000-35000 g / mol.
3. The integrated negative electrode binder for a silicon-based negative electrode according to claim 1, characterized in that: The glass transition temperature Tg of the polymer is 70-110°C.
4. The integrated negative electrode binder for a silicon-based negative electrode according to claim 1, characterized in that: The hydrophilic block in the polyacrylic acid copolymer is selected from one or more of polyethylene glycol, polyoxyethylene ether, polyvinyl alcohol, polyvinyl pyrrolidone, polyacrylamide, sodium polyacrylate, and sodium polystyrene sulfonate; The hydrophobic block in the polyacrylic acid copolymer is selected from one or more of polymethyl methacrylate, polypropylene oxide, polystyrene, polysiloxane, polybutadiene, poly(methyl acrylate) and poly(butyl acrylate).
5. The integrated negative electrode binder for a silicon-based negative electrode according to claim 1, characterized in that: The polyacrylic acid copolymer comprises acrylic acid monomer units, hydrophilic blocks and hydrophobic blocks; the mass ratio of the acrylic acid monomer units, the hydrophilic blocks and the hydrophobic blocks is (10-30): (5-20): (5-10).
6. The integrated negative electrode binder for a silicon-based negative electrode according to claim 5, characterized in that: The polyacrylic acid copolymer further comprises an amide monomer unit and an unsaturated nitrile monomer unit, and the mass ratio of the acrylic acid monomer unit, the amide monomer unit and the unsaturated nitrile monomer unit is (10-30): (5-20): (1-10).
7. An integrated negative electrode binder for a silicon-based negative electrode according to any one of claims 1 to 6, characterized in that: The conductive material is a carbon nanotube; the diameter of the carbon nanotube is 1-30nm, and the aspect ratio is greater than 3000.
8. The integrated negative electrode binder for a silicon-based negative electrode according to claim 1, characterized in that: The mass ratio of the polymer to the conductive material is (5-20): (1-3).
9. A negative electrode sheet, characterized in that: including a negative electrode active material and a binder; The binder comprises the integrated negative electrode binder for silicon-based negative electrode according to any one of claims 1 to 8.
10. A lithium battery, characterized in that: It comprises a positive electrode sheet and the negative electrode sheet as claimed in claim 9.
Citation Information
Cited By
MXene-polymer dual-function bonding composite material for silicon-based negative electrode, preparation method and application of MXene-polymer dual-function bonding composite material
CN122417851A